Extração de DNA de plantas do Cerrado: metodologia inédita e eficiente - Souza, Diego Cerveira de (2019)
The biome Cerrado is the richest savanna in the world in biodiversity, being considered one of the 35 hotspots worldwide, which are priority areas for conservation by the high rate of degradation and number of endemic species. Several species of the biome also have potential for economic use, for food, wood, ornamental and medicinal purposes. However, Cerrado plants are generally rich in secondary compounds, especially phenolic compounds, which make it difficult to extract DNA in sufficient quantity and quality for molecular analyzes, essential for conservation or breeding programs. The extraction methods described to date often do not fit the characteristics of these species and/or are time consuming, expensive and use toxic reagents. So, the present study aims to develop a new and efficient method for extracting DNA from Cerrado plants, in a faster, cheaper and safer way, as well as the comparison of the time and costs involved in the protocol described here and in those already tested for Cerrado plant species. Our method, based on the combined use of SDS and Triton X-100, eliminates the need for multiple purification steps and reduces the use of expensive and/or toxic reagents. For the tests, 10 representative plant species of the Cerrado biome were selected. The quality and quantity of extracted DNA were analyzed by spectrophotometer and agarose gel and its suitability for molecular studies evaluated through restriction enzyme digestion and PCR amplification with RAPD marker. The DNA obtained by our method was intact, free of contaminants and excellent for digestion and amplification via PCR. The DNA concentration among the species tested ranged from 156 to 1166 ng.μL-1 and the A260/A280 ratio of 1.78 to 1.92. Our protocol has also proved to be faster and cheaper compared to the DNA extraction methods already tested for Cerrado species. Therefore, the protocol presented here will be an important tool for the molecular analysis of Cerrado species.